Controllable micro-crosslinking modified high-impact high-density polyethylene composite material and preparation method thereof

By introducing one-dimensional nanomaterials and redox crosslinking agents into high-density polyethylene to build a three-dimensional network structure, the problem of poor toughness of high-density polyethylene is solved, and its impact resistance and toughness is significantly improved. It is suitable for high-impact products.

CN120209466APending Publication Date: 2025-06-27WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202311799420.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The existing high-density polyethylene has poor toughness, which limits its application in the field of high impact products.

Method used

Controllable microcrosslinking modification technology is adopted to build a three-dimensional network structure by introducing one-dimensional nanomaterials and redox crosslinking agents into high-density polyethylene, enhancing the interaction between molecular chains, thereby improving the impact resistance of the material.

Benefits of technology

The impact resistance and toughness of high-density polyethylene is significantly improved, the impact strength of the room temperature notched at the simple-supported beam has been increased by more than 150%, and the melt strength and environmental stress crack resistance have also been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004628501220000121
    Figure BDA0004628501220000121
Patent Text Reader

Abstract

The invention discloses a controllable micro-crosslinking modified high-impact high-density polyethylene composite material and a preparation method thereof. The composite material comprises high-density polyethylene resin, a one-dimensional nano material / maleic anhydride grafted polyethylene master batch, a redox cross-linking agent and a cross-linking assistant. The one-dimensional nano-material serves as a stress concentration point in the matrix and plays a role in absorbing a large amount of energy, so that the impact resistance of the material is improved; the controllability of micro-crosslinking is realized through the synergistic effect of an oxidation-reduction crosslinking agent and tetramethylthiuram disulfide, and the impact resistance of the material is further improved through a long-chain branch and a three-dimensional network structure formed by micro-crosslinking; and the crystallinity of the composite material is reduced, so that the impact resistance of the material is obviously improved. Besides, the melt strength and the environmental stress cracking resistance of the material are greatly improved through controllable micro-crosslinking modification, so that the applicability of the high-density polyethylene in the fields of large-volume injection molding parts, large-diameter pipes and the like is enhanced, and the application field of the high-density polyethylene is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of polymer composites, and particularly relates to a controllable micro-crosslinked modified high impact resistance high density polyethylene composite material and a preparation method thereof. Background Art

[0002] With the rapid progress of polymer materials science and technology, various materials represented by general plastics such as polyethylene and polypropylene have penetrated into all aspects of our lives. Among them, high density polyethylene is widely used in fields such as pipelines, films, cable sheaths, automobile manufacturing and military due to its excellent processing performance, wear resistance, electrical insulation, chemical stability and other characteristics. Although the production capacity and demand of high density polyethylene increase year by year, its simple linear structure and relatively high crystallinity determine that the toughness, environmental stress cracking resistance and other properties of high density polyethylene products are poor, which greatly limits the application range of high density polyethylene.

[0003] Toughening modification of high density polyethylene is an effective method to improve its toughness. Commonly used toughening modification methods mainly include elastomer toughening, organic / inorganic rigid particle toughening, nanomaterial toughening, etc. However, elastomer toughening will significantly reduce the rigidity and modulus of the material. Rigid particle toughening can improve the toughness and modulus of the material, but the tensile strength of the material decreases significantly. Therefore, neither of these two technical routes can improve the toughness of high density polyethylene while ensuring its comprehensive properties. In recent years, with the development of nanoscience and nanotechnology, a series of nanomaterials have shown many strange properties in terms of optics, electricity, heat, mechanics and chemistry due to their surface effect, small size effect, volume effect, quantum effect, etc. Nanoscience has gradually been applied in the modification of polymer materials and achieved some good results. Patent CN1094496C discloses a preparation method of a nanocomposite material for enhancing and toughening polyethylene. By adding nanoparticles, a solvent and a surface dispersant into a device with an ultrasonic oscillator or an oscillating stirring device and grinding with a ball mill in the presence of a small amount of solvent to uniformly disperse the dispersant and the nanoparticles, then drying the surface-treated nanoparticles and mixing them with polyethylene on a twin-screw extruder to prepare a masterbatch, and then extruding and pelletizing the masterbatch and polyethylene on a twin-screw extruder to prepare an enhanced and toughened polyethylene composite material. However, this method only involves the enhancement and toughening modification of polyethylene by some zero-dimensional nanomaterials, and the toughening effect is limited. It is necessary to develop a better method to further improve the toughness of high density polyethylene. Summary of the Invention

[0004] The technical problem to be solved by the present invention is the limitation problem that the toughness of the existing high density polyethylene is poor and it cannot be applied in the field of high impact resistance products. The purpose of the present invention is to provide a controllable micro-crosslinked modified high impact resistance high density polyethylene composite material and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, a controllable micro-crosslinked modified high impact high density polyethylene composite material is prepared by reacting raw materials comprising the following components:

[0007] High density polyethylene resin, 80 - 95 parts by weight, preferably 85 - 90 parts by weight,

[0008] Masterbatch, 5 - 20 parts by weight, preferably 10 - 15 parts by weight, the masterbatch comprising a combination of 10wt% - 20wt% of one-dimensional nanomaterials and 80wt% - 90wt% of maleic anhydride grafted polyethylene,

[0009] Redox crosslinking agent, 0.002 - 0.01 parts by weight, preferably 0.004 - 0.008 parts by weight,

[0010] Crosslinking aid, 0.001 - 0.005 parts by weight, preferably 0.002 - 0.004 parts by weight.

[0011] Preferably, in the above controllable micro-crosslinked modified high impact high density polyethylene composite material, the high density polyethylene resin is a butene-1 copolymer with a low degree of branching, having a molecular weight of 20×10 4 ~25×10 4 g / mol, a molecular weight distribution index of 17 - 24, a melt index of 8 - 12 g / 10 min under 21.6 kg conditions, and a powder with an average particle diameter of 100 - 200 μm. Including but not limited to 23050 powder, 7000F powder, 4731B powder, etc.

[0012] Preferably, in the above controllable micro-crosslinked modified high impact high density polyethylene composite material, the preparation method of the masterbatch comprises the following steps: adding one-dimensional nanomaterials, a solvent, and a surface dispersant into a container according to a weight ratio of nanomaterials to solvent of 1:2 - 5 and a weight ratio of nanomaterials to surface dispersant of 1:0.01 - 0.1, dispersing in an ultrasonic oscillator for 30 - 60 min to uniformly disperse the nanomaterials, drying the dispersed nanomaterials in a vacuum oven at 70 - 90°C for 24 - 48 h, and then adding the dried nanomaterials and maleic anhydride grafted polyethylene into a twin-screw extruder for extrusion granulation, with a temperature of 170 - 230°C and a rotation speed of 30 - 90 rpm, to obtain the masterbatch.

[0013] Preferably, in the above controllable micro-crosslinked modified high impact high density polyethylene composite material, the one-dimensional nanomaterials are at least one of nanocellulose and / or carbon nanotubes, 10 - 50 nm wide and 0.5 - 3 μm long after dispersion.

[0014] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, the solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and / or toluene.

[0015] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, the surface dispersant is at least one of ethylene bisstearamide, glycerol monostearate, zinc stearate, calcium stearate, magnesium stearate, barium stearate, and / or microcrystalline wax.

[0016] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, the maleic anhydride grafted polyethylene is DuPont 40E529 extrusion grade maleic anhydride grafted polyethylene.

[0017] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, the redox crosslinking agent is preferably at least one of N,N-dimethylaniline / ammonium persulfate, benzoyl peroxide / sodium metabisulfite, potassium persulfate / ferrous pyrophosphate, tert-butyl hydroperoxide / ferrous chloride, ammonium persulfate / tetraethylenimine, and more preferably benzoyl peroxide / sodium metabisulfite.

[0018] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, the crosslinking aid is preferably tetramethylthiuram disulfide.

[0019] Preferably, in the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, it further comprises raw materials of the following components:

[0020] The main antioxidant, 0.01 to 0.025 parts by weight, preferably 0.012 to 0.018 parts by weight,

[0021] The auxiliary antioxidant, 0.003 to 0.015 parts by weight, preferably 0.005 to 0.012 parts by weight,

[0022] The stearate, 0.005 to 0.0025 parts by weight, preferably 0.01 to 0.002 parts by weight.

[0023] Preferably, the main antioxidant is a hindered phenol type main antioxidant, preferably one or more of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

[0024] Preferably, the auxiliary antioxidant is a phosphite-based auxiliary antioxidant, preferably one or more of tris[2,4-di-tert-butylphenyl]phosphite, tris(nonylphenyl)phosphite, and tetra(2,4-di-tert-butylphenyl-4,4'-biphenyl)-bisphosphate.

[0025] Preferably, the stearate is preferably one or more of calcium stearate and zinc stearate.

[0026] In a second aspect, the present invention provides a method for preparing the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material, comprising the following steps: in proportion,

[0027] (1) Add high density polyethylene resin, masterbatch, redox crosslinking agent, crosslinking aid, main antioxidant, auxiliary antioxidant, and stearate into a high-speed mixer and mix evenly;

[0028] (2) Add the evenly mixed material into a twin-screw extruder for mixing and granulation to obtain a high impact high density polyethylene composite material.

[0029] Preferably, in the above preparation method, the mixing time of the material in the high-speed mixer is 10-20 min, preferably 15 min.

[0030] Preferably, in the above preparation method, the temperature of the twin-screw extruder is 170-230 °C and the rotation speed is 30-90 rpm.

[0031] In a third aspect, the present invention provides a controllable micro-crosslinked modified high impact high density polyethylene composite material prepared by the above preparation method.

[0032] Preferably, the high impact performance of the above-mentioned controllable micro-crosslinked modified high impact high density polyethylene composite material or the high impact high density polyethylene composite material prepared by the above preparation method is obtained through the synergistic effect of one-dimensional nanomaterial toughening and micro-crosslinking modification, and the controllability of its micro-crosslinking is obtained through the synergistic effect of a redox crosslinking agent and tetramethylthiuram disulfide. Its notched Izod impact strength at room temperature is 40-60 kJ / m 2 , which can be increased by more than 150% at most compared with unmodified high density polyethylene.

[0033] Compared with the prior art, the beneficial effects of the technical solution of the present invention are as follows:

[0034] (1) The present invention creatively uses the synergistic effect of redox crosslinking agents and crosslinking aids (tetramethylthiuram disulfide) to conduct controllable micro-crosslinking modification on high-density polyethylene. The oxide in the redox crosslinking agent is used to initiate the cleavage of polyethylene molecular chains to generate free radicals, and the reduction effect of the reducing agent and the crosslinkable ions generated by tetramethylthiuram disulfide are used to control the generation rate of free radicals, thereby controlling the degree of the entire micro-crosslinking. The micro-crosslinking modification constructs a three-dimensional network structure inside the high-density polyethylene resin, enhancing the interaction between molecular chains. When impacted, the energy required for molecular chain cleavage increases, thus improving the impact resistance of the material. Moreover, the toughness of high-density polyethylene is improved through the synergistic effect of one-dimensional nanomaterial toughening and micro-crosslinking modification. One-dimensional nanomaterials are used, dispersed uniformly through a surface dispersant and ultrasonic oscillation, and extruded and pelletized with maleic anhydride grafted polyethylene, improving the dispersibility of the nanomaterials in the high-density polyethylene resin and avoiding agglomeration. The one-dimensional nanomaterials act as stress concentration points in the matrix, absorbing a large amount of energy, thus hindering the development of cracks and improving the impact resistance of the material. In addition, due to the introduction of one-dimensional nanomaterials and the crosslinking of high-density polyethylene molecular chains, the crystallization process of the composite material is affected, and the crystallinity decreases, further improving the impact resistance of the material.

[0035] (2) The high-impact high-density polyethylene composite material of the present invention has excellent comprehensive properties. Compared with unmodified high-density polyethylene, its notched Izod impact strength at room temperature can be increased by more than 150% at most, and it can be widely used in products with high requirements for material impact strength, such as bottles, barrels, boxes, pipes, etc. In addition, the long branched chains and three-dimensional network structure formed by controllable micro-crosslinking modification greatly improve the melt strength and environmental stress cracking resistance of the material, which can be increased by about 53% and 86% respectively at most, enhancing the anti-drooping performance and long-term use performance of the material, making high-density polyethylene more applicable in large-volume injection molded parts such as 200L large intermediate bulk containers and ton barrels, and large-diameter pipes such as water supply pipes with a diameter of more than 800 mm, and extending the service life of high-density polyethylene products, thus broadening the application field of high-density polyethylene. Detailed implementation mode

[0036] The present invention will be further described below through examples, but it should be understood that these examples should not be used to limit the present invention.

[0037] All "parts" mentioned below are parts by weight.

[0038] Example 1

[0039] The raw materials of the controllable micro-crosslinked modified high impact high density polyethylene composite material of this embodiment include the following parts by mass: 95 parts of high density polyethylene (23050 powder, with a melt index of 5-8 g / 10 min for 21.6 kg, Wanhua Chemical Group Co., Ltd.), 5 parts of a masterbatch containing 10% of nanocellulose (nanocellulose dry powder, 10-50 nm wide and 0.5-3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.002 parts of benzoyl peroxide / sodium metabisulfite, 0.005 parts of tetramethylthiuram disulfide, 0.012 parts of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0040] Its preparation method includes the following steps: Add nanocellulose, solvent, and surface dispersant to a container according to a weight ratio of nanomaterials to solvent of 1:4 and a weight ratio of nanomaterials to surface dispersant of 1:0.05, place it in an ultrasonic oscillator for dispersion for 60 min to uniformly disperse the nanomaterials, dry the dispersed nanomaterials in a vacuum oven at 85 °C for 48 h, and then add the dried nanomaterials and DuPont 40E529 extrusion-grade maleic anhydride grafted polyethylene in a weight ratio of 1:8 into a twin-screw extruder for extrusion granulation, with a temperature of 220 °C and a rotation speed of 60 r / min to obtain the masterbatch;

[0041] Take each raw material according to the selected parts by mass, add them to a high-speed mixer and mix evenly, then add the uniformly mixed materials to a twin-screw extruder for mixing and extrusion granulation. The mixing time of the materials in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain the high impact high density polyethylene composite material.

[0042] Example 2

[0043] The raw materials of the controllable micro-crosslinked modified high impact high density polyethylene composite material of this embodiment include the following parts by mass: 90 parts of high density polyethylene (23050 powder, with a melt index of 5-8 g / 10 min for 21.6 kg, Wanhua Chemical Group Co., Ltd.), 10 parts of a masterbatch containing 10% of nanocellulose (nanocellulose dry powder, 10-50 nm wide and 0.5-3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.004 parts of benzoyl peroxide / sodium metabisulfite, 0.002 parts of tetramethylthiuram disulfide, 0.012 parts of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0044] The preparation method comprises the following steps: Add nanocellulose, a solvent, and a surface dispersant into a container according to a weight ratio of nanomaterials to the solvent of 1:4 and a weight ratio of nanomaterials to the surface dispersant of 1:0.05, place it in an ultrasonic oscillator for dispersion for 60 min to uniformly disperse the nanomaterials, dry the dispersed nanomaterials in a vacuum oven at 85 °C for 48 h, and then add the dried nanomaterials and DuPont 40E529 extrusion-grade maleic anhydride grafted polyethylene into a twin-screw extruder according to a weight ratio of 1:8 for extrusion granulation at a temperature of 220 °C and a rotation speed of 60 r / min to obtain a masterbatch;

[0045] Take each raw material according to the selected mass fraction and add it into a high-speed mixer for uniform mixing. Add the uniformly mixed material into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the material in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain a high impact high density polyethylene composite material.

[0046] Example 3

[0047] The raw materials of the controllable micro-crosslinked modified high impact high density polyethylene composite material in this example include the following mass fractions: 85 parts of high density polyethylene (23050 powder, melt index of 5 - 8 g / 10 min, 21.6 kg, Wanhua Chemical Group Co., Ltd.), 15 parts of a masterbatch with a content of 10% of nanocellulose (nanocellulose dry powder, 10 - 50 nm wide and 0.5 - 3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.006 parts of benzoyl peroxide / sodium metabisulfite, 0.003 parts of tetramethylthiuram disulfide, 0.012 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0048] The preparation method comprises the following steps: Add nanocellulose, a solvent, and a surface dispersant into a container according to a weight ratio of nanomaterials to the solvent of 1:4 and a weight ratio of nanomaterials to the surface dispersant of 1:0.05, place it in an ultrasonic oscillator for dispersion for 60 min to uniformly disperse the nanomaterials, dry the dispersed nanomaterials in a vacuum oven at 85 °C for 48 h, and then add the dried nanomaterials and DuPont 40E529 extrusion-grade maleic anhydride grafted polyethylene into a twin-screw extruder according to a weight ratio of 1:8 for extrusion granulation at a temperature of 220 °C and a rotation speed of 60 r / min to obtain a masterbatch; Take each raw material according to the selected mass fraction and add it into a high-speed mixer for uniform mixing. Add the uniformly mixed material into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the material in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain a high impact high density polyethylene composite material.

[0049] Example 4

[0050] The raw materials of the controllable micro-crosslinked modified high impact high density polyethylene composite material in this example include the following parts by mass: 80 parts of high density polyethylene (23050 powder, melt index 5-8 g / 10 min of 21.6 kg, Wanhua Chemical Group Co., Ltd.), 20 parts of masterbatch with a content of 10% of nanocellulose (nanocellulose dry powder, 10-50 nm wide and 0.5-3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.008 parts of benzoyl peroxide / sodium metabisulfite, 0.004 parts of tetramethylthiuram disulfide, 0.012 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0051] Its preparation method includes the following steps: Add nanocellulose, solvent, and surface dispersant into a container according to the weight ratio of nanomaterials to solvent of 1:4 and the weight ratio of nanomaterials to surface dispersant of 1:0.05, place it in an ultrasonic oscillator for 60 min to disperse the nanomaterials evenly, dry the dispersed nanomaterials in a vacuum oven at 85 °C for 48 h, and then add the dried nanomaterials and DuPont 40E529 extrusion-grade maleic anhydride grafted polyethylene in a weight ratio of 1:8 into a twin-screw extruder for extrusion granulation at a temperature of 220 °C and a rotation speed of 60 r / min to obtain the masterbatch; Take each raw material according to the selected parts by mass and add them into a high-speed mixer to mix evenly, add the evenly mixed materials into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the materials in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain the high impact high density polyethylene composite material.

[0052] Example 5

[0053] The raw materials of the controllable micro-crosslinked modified high impact high density polyethylene composite material in this example include the following parts by mass: 90 parts of high density polyethylene (23050 powder, melt index 5-8 g / 10 min of 21.6 kg, Wanhua Chemical Group Co., Ltd.), 10 parts of masterbatch with a content of 10% of nanocellulose (nanocellulose dry powder, 10-50 nm wide and 0.5-3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.01 parts of benzoyl peroxide / sodium metabisulfite, 0.001 parts of tetramethylthiuram disulfide, 0.012 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0054] The preparation method includes the following steps: Add nanocellulose, solvent, and surface dispersant into a container according to the weight ratio of nanomaterials to solvent being 1:4 and the weight ratio of nanomaterials to surface dispersant being 1:0.05. Place it in an ultrasonic oscillator for 60 minutes to disperse the nanomaterials evenly. Dry the well-dispersed nanomaterials in a vacuum oven at 85°C for 48 hours. Then add the dried nanomaterials and DuPont 40E529 extrusion-grade maleic anhydride-grafted polyethylene in a weight ratio of 1:8 into a twin-screw extruder for extrusion granulation at a temperature of 220°C and a rotation speed of 60 r / min to obtain the masterbatch. Take each raw material according to the selected mass parts and add them into a high-speed mixer to mix evenly. Add the evenly mixed materials into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the materials in the high-speed mixer is 15 minutes, the temperature of the extruder is 220°C, and the screw rotation speed is 60 r / min to obtain the high impact high density polyethylene composite material.

[0055] Comparative Example 1

[0056] The raw materials of the high impact high density polyethylene composite material in this comparative example include the following mass parts: 90 parts of high density polyethylene (23050 powder, with a melt index of 5 - 8 g / 10 min and a weight of 21.6 kg, Wanhua Chemical Group Co., Ltd.), 0.012 parts of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0057] The preparation method includes the following steps: Take each raw material according to the selected mass parts and add them into a high-speed mixer to mix evenly. Add the evenly mixed materials into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the materials in the high-speed mixer is 15 minutes, the temperature of the extruder is 220°C, and the screw rotation speed is 60 r / min to obtain the high impact high density polyethylene composite material.

[0058] Comparative Example 2

[0059] The raw materials of the high impact high density polyethylene composite material in this comparative example include the following mass parts: 90 parts of high density polyethylene (23050 powder, with a melt index of 5 - 8 g / 10 min and a weight of 21.6 kg, Wanhua Chemical Group Co., Ltd.), 10 parts of a masterbatch with a 10% content of nanocellulose (nanocellulose dry powder, 10 - 50 nm wide and 0.5 - 3 μm long after dispersion, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.), 0.012 parts of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.005 parts of tris(2,4-di-tert-butylphenyl) phosphite, and 0.01 parts of calcium stearate.

[0060] The preparation method comprises the following steps: Add nanocellulose, a solvent, and a surface dispersant into a container according to a weight ratio of the nanomaterial to the solvent of 1:4 and a weight ratio of the nanomaterial to the surface dispersant of 1:0.05, place it in an ultrasonic oscillator for dispersion for 60 min to uniformly disperse the nanomaterial, dry the dispersed nanomaterial in a vacuum oven at 85 °C for 48 h, and then add the dried nanomaterial and DuPont 40E529 extrusion-grade maleic anhydride grafted polyethylene in a weight ratio of 1:8 into a twin-screw extruder for extrusion granulation at a temperature of 220 °C and a rotation speed of 60 r / min to obtain a masterbatch; Take each raw material according to the selected mass parts and add them into a high-speed mixer for uniform mixing, add the uniformly mixed material into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the material in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain a high impact high density polyethylene composite material.

[0061] Comparative Example 3

[0062] The raw materials of the high impact high density polyethylene composite material in this comparative example include the following mass parts: 90 parts of high density polyethylene (23050 powder, melt index 5 - 8 g / 10 min, 21.6 kg, Wanhua Chemical Group Co., Ltd.), 0.004 part of benzoyl peroxide / sodium metabisulfite, 0.002 part of 1,2 - divinylbenzene, 0.012 part of pentaerythritol tetra[β-(3,5 - di - tert - butyl - 4 - hydroxyphenyl)propionate], 0.005 part of tris(2,4 - di - tert - butylphenyl) phosphite, 0.01 part of calcium stearate.

[0063] The preparation method comprises the following steps: Take each raw material according to the selected mass parts and add them into a high-speed mixer for uniform mixing, add the uniformly mixed material into a twin-screw extruder for mixing and extrusion granulation. The mixing time of the material in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw rotation speed is 60 r / min to obtain a high impact high density polyethylene composite material.

[0064] Comparative Example 4

[0065] The raw materials of the controllable micro - crosslinked modified high impact high density polyethylene composite material in this example include the following mass parts: 90 parts of high density polyethylene (23050 powder, melt index 5 - 8 g / 10 min, 21.6 kg, Wanhua Chemical Group Co., Ltd.), 0.004 part of benzoyl peroxide / sodium metabisulfite, 0.002 part of tetramethylthiuram disulfide, 0.012 part of pentaerythritol tetra[β-(3,5 - di - tert - butyl - 4 - hydroxyphenyl)propionate], 0.005 part of tris(2,4 - di - tert - butylphenyl) phosphite, 0.01 part of calcium stearate.

[0066] The preparation method comprises the following steps: taking each raw material according to the selected mass parts, adding them into a high-speed mixer and mixing evenly, adding the evenly mixed materials into a twin-screw extruder for kneading, and extruding and pelletizing. The mixing time of the materials in the high-speed mixer is 15 min, the temperature of the extruder is 220 °C, and the screw speed is 60 r / min, to obtain a high impact-resistant high-density polyethylene composite material.

[0067] Performance testing

[0068] The high impact-resistant high-density polyethylene composite materials prepared in Examples 1-5 and Comparative Examples 1-4 are made into test specimens, and the performance testing is carried out according to the following method:

[0069] For the tensile strength and elongation at break testing, a tensile test is carried out according to the method of GB / T 1040-92;

[0070] For the flexural modulus testing, a flexural test is carried out according to the method of GB / T 1449-2005;

[0071] The notched Izod impact strength of simply supported beams is tested according to the requirements of the impact test method of national standard GB / T 1043.1-2008;

[0072] For the melt strength testing, a melt strength test is carried out according to the method of GB / T 2951.41-2008;

[0073] The environmental stress cracking resistance is tested according to GB / T 1842-1999.

[0074] The specific test results are shown in Table 1.

[0075] Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-4

[0076]

[0077] As can be seen from Table 1, by comparing the test data of Examples 1-5 with those of Comparative Examples 1-4, it can be found that the comprehensive properties of the high impact high density polyethylene composites in Examples 1-5 have been significantly improved, especially the notched Izod impact strength, melt strength and environmental stress cracking resistance. This is because the micro-crosslinking modification constructs long branched chains and three-dimensional network structures inside the high density polyethylene resin, enhancing the interaction between molecular chains. When impacted, the energy required for molecular chain breakage increases, thus improving the impact resistance of the material. The one-dimensional nanomaterials uniformly dispersed in the high density polyethylene resin act as stress concentration points in the matrix, absorbing a large amount of energy, thus hindering the development of cracks and improving the impact resistance of the material. In addition, due to the introduction of one-dimensional nanomaterials and the crosslinking of high density polyethylene molecular chains, the crystallization process of the composite material is affected and the crystallinity decreases, further improving the impact resistance of the material. The long branched chains and three-dimensional network structures formed by micro-crosslinking modification increase the entanglement between molecular chains, thus improving both the melt strength and environmental stress cracking resistance of the material.

[0078] From the comparison between Example 2 and Comparative Examples 1-3, it can be seen that the synergistic effect of the redox crosslinking agent and tetramethylthiuram disulfide can precisely control the degree of micro-crosslinking by adjusting the addition amount of the redox crosslinking agent, so as to prepare a composite material with the target crosslinking degree. This is because in the redox crosslinking agent and tetramethylthiuram disulfide system, the oxide in the redox crosslinking agent is used to initiate the breakage of polyethylene molecular chains to generate free radicals, and the reduction effect of the reducing agent and the crosslinkable ions generated by tetramethylthiuram disulfide are used to control the generation rate of free radicals, thus effectively controlling the degree of micro-crosslinking of the material.

[0079] Obviously, the above examples are only for clear illustration and not limitations on the implementation modes. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation modes here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A controllable micro-crosslinked modified high impact density polyethylene composite material is prepared by reacting raw materials comprising the following components: High density polyethylene resin, 80 - 95 parts by weight, preferably 85 - 90 parts by weight; Masterbatch, 5 - 20 parts by weight, preferably 10 - 15 parts by weight, the masterbatch comprising a combination of 10wt% - 20wt% of one-dimensional nanomaterials and 80wt% - 90wt% of maleic anhydride grafted polyethylene; Redox crosslinking agent, 0.002 - 0.01 parts by weight, preferably 0.004 - 0.008 parts by weight; Crosslinking aid, 0.001 - 0.005 parts by weight, preferably 0.002 - 0.004 parts by weight.

2. The composite material according to claim 1, wherein The high-density polyethylene resin is a butene-1 copolymer with low branching degree, having a molecular weight of 20×10 4 ~25×10 4 g / mol, a molecular weight distribution index of 17-24, a melt index of 8-12 g / 10 min under the condition of 21.6 kg, and a powder with an average particle size of 100-200 μm, preferably one or more of the 23050 powder, 7000F powder, and 4731B powder.

3. The composite material according to claim 1 or 2, characterized in that, The one-dimensional nanomaterials are at least one of nanocellulose and / or carbon nanotubes, 10 - 50 nm wide and 0.5 - 3 μm long after dispersion.

4. The composite material according to any one of claims 1-3, characterized in that, The maleic anhydride grafted polyethylene is the extrusion grade maleic anhydride grafted polyethylene of DuPont 40E529 in the United States.

5. The composite material according to any one of claims 1-4, characterized in that, The preparation method of the masterbatch comprises the following steps: adding the one-dimensional nanomaterials, solvent, and surface dispersant into a container according to the weight ratio of nanomaterials to solvent of 1:2 - 5 and the weight ratio of nanomaterials to surface dispersant of 1:0.01 - 0.1, placing it in an ultrasonic oscillator for dispersion for 30 - 60 min to uniformly disperse the nanomaterials, drying the dispersed nanomaterials in a vacuum oven at 70 - 90°C for 24 - 48 h, and then adding the dried nanomaterials and maleic anhydride grafted polyethylene into a twin-screw extruder for extrusion granulation at a temperature of 170 - 230°C and a rotation speed of 30 - 90 rpm to obtain the masterbatch.

6. The composite material according to any one of claims 1-5, characterized in that, The redox crosslinking agent is at least one of N,N-dimethylaniline / ammonium persulfate, benzoyl peroxide / sodium metabisulfite, potassium persulfate / ferrous pyrophosphate, tert-butyl hydroperoxide / ferrous chloride, ammonium persulfate / tetraethylenimine, preferably benzoyl peroxide / sodium metabisulfite.

7. The composite material according to any one of claims 1-6, characterized in that, The crosslinking aid is preferably tetramethylthiuram disulfide.

8. The composite material according to any one of claims 1-7, characterized in that, The composite material further comprises raw materials of the following components: Primary antioxidant, 0.01 - 0.025 parts by weight, preferably 0.012 - 0.018 parts by weight, Secondary antioxidant, 0.003 - 0.015 parts by weight, preferably 0.005 - 0.012 parts by weight, Stearate, 0.005 - 0.0025 parts by weight, preferably 0.01 - 0.002 parts by weight.

9. The composite material according to claim 8, characterized in that, The primary antioxidant is a hindered phenol primary antioxidant, preferably one or more of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; and / or, The secondary antioxidant is a phosphite secondary antioxidant, preferably one or more of tris(2,4-di-tert-butylphenyl) phosphite, tris(nonylphenyl) phosphite, and tetra(2,4-di-tert-butylphenyl-4-4'-biphenyl)-bisphosphite; and / or, The stearate is one or more of calcium stearate and zinc stearate.

10. A method for preparing the controllable micro-crosslinked modified high impact high density polyethylene composite material according to any one of claims 1-9, comprising the following steps: According to the proportion, (1) Add high-density polyethylene resin, masterbatch, redox crosslinking agent, crosslinking aid, primary antioxidant, secondary antioxidant, and stearate into a high-speed mixer and mix evenly. (2) Add the evenly mixed material into a twin-screw extruder for mixing and extrusion granulation to obtain a high impact-resistant high-density polyethylene composite material.

Citation Information

Patent Citations

  • Process for preparing nano particles reinforced and toughened polyethylene composition

    CN1094496C

Cited By

  • High-strength torsion-resistant cable sheath material based on polyurethane / crosslinked polyethylene as well as preparation method and application of high-strength torsion-resistant cable sheath material

    CN121736474A